Transparent glass ceramics from 65LiNbO3-35SiO2 glass composition - P. Prapitpongwanich (2018)
Transparent glass with composition 65LiNbO3-35SiO2 was fabricated via the conventional melt-quenching technique. Glass-ceramics containing nanoscale (less than 100 nm) rhombohedral lithium niobate crystals were successfully produced by annealing the respective glass at various temperatures (600, 650 700 and 975 °C) for 1 h. The result of optical transmission spectra shows that the quenched sample is optically transparent. Transparent samples should possess crystals « 200 nm and have a narrow distribution of crystal sizes. © 2008 Trans Tech Publications, Switzerland.